Differential intolerance to loss of function and missense mutations in genes that encode human matricellular proteins - Kaur, Sukhbir (J Cell Commun Signal, 2021)
Targeted gene disruption in mice has provided valuable insights into the functions of matricellular proteins. Apart from missense and loss of function mutations that have been associated with inherited diseases, however, their functions in humans remain unclear. The availability of deep exome sequencing data from over 140,000 individuals in the Genome Aggregation Database provided an opportunity to examine intolerance to loss of function and missense mutations in human matricellular genes. The probability of loss-of-function intolerance (pLI) differed widely within members of the thrombospondin, CYR61/CTGF/NOV (CCN), tenascin, small integrin-binding ligand N-linked glycoproteins (SIBLING), and secreted protein, acidic and rich in cysteine (SPARC) gene families. Notably, pLI values in humans had limited correlation with viability of the corresponding homozygous null mice. Among the thrombospondins, only THBS1 was highly loss-intolerant (pLI = 1). In contrast, Thbs1 is not essential for viability in mice. Several known thrombospondin-1 receptors were similarly loss-intolerant, although thrombospondin-1 is not the exclusive ligand for some of these receptors. The frequencies of missense mutations in THBS1 and the gene encoding its signaling receptor CD47 indicated conservation of some residues implicated in specific receptor binding. Deficits in missense mutations were also observed for other thrombospondin genes and for SPARC, SPOCK1, SPOCK2, TNR, and DSPP. The intolerance of THBS1 to loss of function in humans and elevated pLI values for THBS2, SPARC, SPOCK1, TNR, and CCN1 support important functions for these matricellular protein genes in humans, some of which may relate to functions in reproduction or responding to environmental stresses.